Fracture of brittle solids under impact: The decisive role of stress waves. (March 2022) - Jiang, Bin; Hu, Jiayi; Guo, Yazhou; Li, Jian; Ding, Yi; Wei, Qiuming; Suo, Tao; Li, Yulong
Highlights: A new factor, stress wave, that determines the impact strength of brittle solids is revealed for the first time. Effects of two loading stress waves are studied by electromagnetic SHPB (ESHPB) apparatus. One is traditional uniaxial-unidirectional (UD) and the other is uniaxial-bidirectional (BD). With all other loading conditions identical, the UD stress wave resulted in 69% higher compressive strength compared with BD stress wave. The findings pose new challenges on strength model, experimental technique and structure design of brittle materials. Abstract: Measurement of the impact strength of brittle solids is traditionally conducted by split Hopkinson pressure bar (SHPB), where one stress wave is generated and loads on the specimen (uniaxial-unidirectional, UD). What if this single stress wave is split into two (or more) smaller pulses that load on the same specimen? Based on the classical one dimensional elastic stress wave theory, nothing different would happen. However, our experiments revealed the opposite results. Electromagnetic split Hopkinson pressure bar (ESHPB), a newly developed technique that can launch two stress pulses simultaneously in opposite directions along the coaxial bars (uniaxial-bidirectional, BD), was adopted to test the compressive strength of a glass. Results indicated that the loading stress waves largely determined the measured compressive strength, with all other conditions identical. Significant discrepancy (as large as 69.1%) was observed between UD and BD strength. Possible reason for this discrepancy was proposed by high-speed photography.